The Effect of the Snowball Throwing Learning Model on the Learning Outcomes of Pancasila Education of Grade III Students of SD Negeri 098166 Perumnas Batu VI - Fitri Ankelima Sianturi; Eva Pasaribu; Aprido Bernando Simamora (International Journal of Technology and Education Research, 2026)
The purpose of this study was to determine the effect of the Snowball Throwing Learning Model on the learning outcomes of Pancasila Education of third-grade students of SD Negeri 098166 Perumnas Batu VI. This study is a quantitative study using a pre-experimental design in the form of One Group Pretest-Posttest Design. The sample in this study amounted to 25 students. The data collection technique used a multiple-choice test. Before being given treatment, a pretest was conducted with an average value of 57.92. After being given treatment using the Snowball Throwing learning model, a posttest score was obtained with an average of 87.36. This shows that the posttest score is higher than the pretest score so that there is an increase in student learning outcomes. The results of the normality test using the Shapiro-Wilk test show that the pretest data has a significance value of 0.054 and the posttest is 0.056. Because both significance values ​​are greater than 0.05, it can be concluded that the data is normally distributed. Based on the results of the N-Gain test, an average value of 0.7167 is obtained which is included in the high category. Furthermore, the results of the hypothesis test (t-test) obtained a calculated t value of 30.148 with a significance level of 0.000. Because the significance value is less than 0.05 and the calculated t value > t table (30.148 > 1.711), H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an effect of the Snowball Throwing learning model on the learning outcomes of Pancasila Education for third-grade students of SD Negeri 098166 Perumnas Batu VI in the 2025/2026 academic year.